Osmotic Balance Regulates Cell Fusion during Mating in Saccharomyces cerevisiae - Philips, Jennifer (The Rockefeller University Press, 1997)

(untitled)
Successful zygote formation during yeast mating requires cell fusion of the two haploid mating partners. To ensure that cells do not lyse as they remodel their cell wall, the fusion event is both temporally and spatially regulated: the cell wall is degraded only after cell–cell contact and only in the region of cell–cell contact. To understand how cell fusion is regulated, we identified mutants defective in cell fusion based upon their defect in mating to a fus1 fus2 strain (Chenevert, J., N. Valtz, and I. Herskowitz. 1994. Genetics 136:1287–1297). Two of these cell fusion mutants are defective in the FPS1 gene, which codes for a glycerol facilitator (Luyten, K., J. Albertyn, W.F. Skibbe, B.A. Prior, J. Ramos, J.M. Thevelein, and S. Hohmann. 1995. EMBO [Eur. Mol. Biol. Organ.] J. 14:1360–1371). To determine whether inability to maintain osmotic balance accounts for the defect in cell fusion in these mutants, we analyzed the behavior of an fps1Δ mutant with reduced intracellular glycerol levels because of a defect in the glycerol-3-phosphate dehydrogenase (GPD1) gene (Albertyn, J., S. Hohmann, J.M. Thevelein, and B.A. Prior. 1994. Mol. Cell. Biol. 14:4135– 4144): deletion of GPD1 partially suppressed the cell fusion defect of fps1 mutants. In contrast, overexpression of GPD1 exacerbated the defect. The fusion defect could also be partially suppressed by 1 M sorbitol. These observations indicate that the fusion defect of fps1 mutants results from inability to regulate osmotic balance and provide evidence that the osmotic state of the cell can regulate fusion. We have also observed that mutants expressing hyperactive protein kinase C exhibit a cell fusion defect similar to that of fps1 mutants. We propose that Pkc1p regulates cell fusion in response to osmotic disequilibrium. Unlike fps1 mutants, fus1 and fus2 mutants are not influenced by expression of GPD1 or by 1 M sorbitol. Their fusion defect is thus unlikely to result from altered osmotic balance.